‘It’s All in Their Brain’: Constructing the figure of the trafficking victim on the US-Mexico border - Sanchez, Gabriella (Anti-Trafficking Review, 2016)
This article is a qualitative reflection on a series of human trafficking awareness meetings held in a city on the US-Mexico border. It argues that along this border, representations of the human trafficking victim go beyond the stereotypical notions of the virginal female youth, target of sexual exploitation and violence. Rather, characterisations reflect a specific set of cultural and historical forms which further frame victims as inherently foreign, a proxy for Mexican, despite the ethnic similarities connecting communities on both sides of the US-Mexico divide. References to Mexican origin in this part of the United States have historically been used as part of an attempt to articulate social and ethnic difference, often despite sharing a common ethnic past. In the context of American anti-immigrant sentiments, Mexicans are described not only as inherently foreign, or as lacking government-sanctioned immigration status, but also as innately uncivilised, uneducated, hypersexual, criminal and pathological. On the US-Mexico border these characterisations become further complicated by the immediacy of Mexican border cities and their ongoing struggles amid the war on drugs. Collectively, the tropes of crime, violence and inherent pathos historically associated with Mexico and its people have seeped into the construction of the human trafficking rhetoric on the border, and have been quickly and effectively disseminated, despite the absence of empirically-informed indicators. Furthermore, while this practice is reflective of the efforts through which historically Mexican nationals have been othered along the US-Mexico border, in the current context of globalised fears over migrants and national security, human trafficking constructions become another tool of US border control and migration governance.